Laparoscopic Radical Hysterectomy Results in Higher Recurrence Rate Versus Open Abdominal Surgery for Stage IB1 Cervical Cancer Patients With Tumor Size Less Than 2 Centimeter: A Retrospective Propensity Score-Matched Study - Chen, Xiaoyue; Yu, Jiangtao; Zhao, Hongqin; Hu, Yan; Zhu, Haiyan (Frontiers in Oncology, 2021)
Objective: To compare the oncologic outcomes between laparoscopic and open radical hysterectomy in patients with stage ⅠB1 cervical cancer lesion less than 2 cm. Methods: Patients diagnosed FIGO (2009) stage IB1 (tumor diameter<2 cm) and underwent radical hysterectomy in our hospital between March 2008 and November 2018 were studied. A propensity-matched comparison (1:2) was conducted to minimize selection biases. Demographic and baseline oncologic characteristics were balanced between groups. Overall survival (OS) and disease-free survival (DFS) were assessed using the Kaplan–Meier model, along with univariable and multivariable regression analysis. Results: A total of 261 patients were enrolled in this study after propensity-matching, with 174 in the open group and 87 in the laparoscopic group. Disease relapsed in 7 patients in laparoscopy group, and the recurrence rate was 8.0% (7/87). There were 8 patients underwent abdominal radical hysterectomy experienced recurrence, and the recurrence rate was 4.6% (8/174). The multivariate analysis model revealed that laparoscopic operation was associated with higher risk of recurrence than abdominal radical hysterectomy (HR, 3.789; 95% CI, 1.143-12.559; p=0.029). There were 5 patients or 2.9% (5/174) died in open surgery group and the corresponding percentage in laparoscopy group was 2.3% (2/87). No difference was found in OS between the two groups (HR, 1.823; 95% CI, 0.2673-12.44; log-rank p = 0.5398). All the recurrence occurred within two years after operation in the laparoscopy group, among which pelvic recurrence (85.7%) was dominant. Conclusion: Traditional laparotomy radical hysterectomy has a lower recurrence rate when compared with laparoscopic operation in those cervical cancer patients with a foci diameter less than 2cm. However, no detrimental effect on survival was found in minimal invasive operation group. Further multi-center prospective trials are needed to confirm our results on a large scale.